Fast track to failure? Energy transition minerals and the future of consultation and consent. (July 2022) - Owen, John R.; Kemp, Deanna; Harris, Jill; Lechner, Alex M.; Lèbre, Éléonore
Abstract: Energy transition mineral and metals (ETM) are being widely discussed for their utility in combating climate change. However, their contribution with respect to social and environmental impact does not feature prominently in contemporary debates. In this paper we present findings showing the extent to which the world's ETM projects will intersect with Indigenous Peoples' and Peasant lands – the lands of people who under existing United Nations-level declarations have explicit consultation and consent rights. Our results suggest that the majority of the world's ETM projects are located either on or near Indigenous Peoples' or Peasant lands with adverse conditions for human rights-compatible permitting, consultation, and consent. The implications are profound in terms of understanding the basis on which agreed international safeguards may be diluted in the rush to meet market demand, and that the extent to which the future supply of ETMs will exacerbate social inequalities in already vulnerable locations. Highlights: Mining projects being fast-tracked to supply 'energy transition minerals' (ETM) Majority of ETM projects located on the lands of rights-holding groups Explores the relative quality of institutional safeguards and supports Project locations indicate adverse conditions for permitting, consultation, and consent. Method tests the limits of what is analytically possible, given available global data.